Coarse-grained modelling of a DNA origami force sensor - Sen, N (2021)
We have simulated large-scale DNA nanostructures using the oxDNA software which uses coarse-graining at the nucleotide level. These simulations can complement experiments as they typically allow greater structural resolution and give access to a range of properties that are otherwise hard to measure (e.g. internal forces).